Evidence for a polygenic contribution to androgenetic alopecia. (10th October 2013) - Heilmann, S.; Brockschmidt, F.F.; Hillmer, A.M.; Hanneken, S.; Eigelshoven, S.; Ludwig, K.U.; Herold, C.; Mangold, E.; Becker, T.; Kruse, R.; Knapp, M.; Nöthen, M.M.
Summary Background Male pattern baldness (androgenetic alopecia, AGA) is a highly heritable trait and the most common form of hair loss in humans. Eight genome‐wide significant risk loci for AGA have been identified. Objectives To determine whether a polygenic component contributes to the genetic risk for AGA. Methods This study used a German case–control sample for AGA, which comprised 581 severely affected patients and 617 controls, to determine the contribution of polygenic variance to AGA risk. The sample was divided evenly into discovery and test samples. An additive polygenic risk score was calculated from risk alleles with increasingly liberal P‐values in the discovery dataset, which was then used to test for the enrichment of AGA risk score alleles in the independent test samples. Results The polygenic score analysis provided significant evidence for a polygenic contribution to AGA where the amount of variance explained was 1·4–4·5%. Conclusion This study provides evidence for the specific contribution of a polygenic component to the overall heritable risk for AGA. To some degree, the polygenic architecture of AGA might reflect the complexity of the biological pathways involved. Further analyses and strategies that complement conventional genome‐wide association studies are needed to identify these factors. These may include pathway‐based analyses, the analysis of functional candidate genes and tests for epistatic effects with known loci.